1982
DOI: 10.1136/bmj.284.6312.309-a
|View full text |Cite
|
Sign up to set email alerts
|

Toxocaral and toxoplasmal antibodies in cat breeders and in Icelanders exposed to cats but not to dogs.

Abstract: 8Platts-Mills TAE, Snajdr MI, Ishizaka K, Frankland AW. Measurement of IgE antibody by an antigen-binding assay; correlation with PK activity and IgG and IgA antibodies to allergens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…In India, boys had double the infection rate (41.9%) of girls (20.4%) in the 1 to 16 years old age group [14] which was similar to that reported in children in Brazil, with 66.7% prevalence in boys and 33.3% in girls [8]. The eradication of dogs in Iceland during the forties resulted in the disappearance of Toxocariasis in humans by the early eighties [17]. A study in Brazil showed an association between increased levels of Toxocara antibodies in children and the presence of young dogs and contact with their feces [7].…”
Section: Discussionmentioning
confidence: 54%
“…In India, boys had double the infection rate (41.9%) of girls (20.4%) in the 1 to 16 years old age group [14] which was similar to that reported in children in Brazil, with 66.7% prevalence in boys and 33.3% in girls [8]. The eradication of dogs in Iceland during the forties resulted in the disappearance of Toxocariasis in humans by the early eighties [17]. A study in Brazil showed an association between increased levels of Toxocara antibodies in children and the presence of young dogs and contact with their feces [7].…”
Section: Discussionmentioning
confidence: 54%
“…1978). Nevertheless, the presence of dogs seems to be important for the determination of human infection, as the eradication of dogs in Iceland during the 1940s led to the disappearance of human Toxocara infection in that country at the beginning of the 1980s (Woodruff et al. 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors reported a higher frequency of infection for individuals who maintained contact with dogs (Matsumura & Endo 1983); while others found no association of ownership and professional contact with dogs with the frequency of Toxocara infection (Woodruff et al 1978). Nevertheless, the presence of dogs seems to be important for the determination of human infection, as the eradication of dogs in Iceland during the 1940s led to the disappearance of human Toxocara infection in that country at the beginning of the 1980s (Woodruff et al 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of stray or shelter animals the source of infection is probably environmental. 616,636,637 Other reported risk factors for seroconversion include pica, living in rural areas, visiting a playground frequently, developmental delay in children, reduced IQ scores in children, low socioeconomic status, frequent playing in a sandbox, and frequent contact with soil. 631 -633 It is unclear whether the apparent risk of pet ownership is because of household environmental contamination that results from owning a dog or whether there may be other factors involved such as increased exposure to potentially contaminated external environmental sites (i.e., public parks) in dog -owning families.…”
Section: Dogs and C Atsmentioning
confidence: 99%